The Effect of Learning Organisation Practices in Cottage and Small Industries in Diktel Rupakot Majhuwagadhi Municipality - Rai, Bijaya Kumar (DMC Journal, 2025)
This study primarily aims to examine learning organisation practices, assess their effectiveness, and explore the relationships between the dimensions of learning organisation and the performance of cottage and small industries in Diktel Rupakot Majhuwagadhi Municipality (DRMM). In research methodology, a simple convenience sampling technique was used for primary data collection. The sample size was determined as158 using Yamane's formula (N/(1+N(e)2) with a fixed margin of error of 5 per cent, based on 260 registered and authentic firms. The administered questionnaire was distributed accordingly; however, only 127 respondents were received and deemed valid for analysis. The reliability and validity test of the collected data, as well as data processing and analysis, were conducted using IBM Statistical Packages for Social Sciences (SPSS) version 27 software. The findings of this study indicate that the multivariate test analysis is statistically significant (p<0.001). The practices of learning organisation are found to be effective, as indicated by the F-test result (F=529.589. The analysis shows an average level of correlation between dimensions of learning organisation and cottage in small industries. Likewise, various statistical tests reveal that the effectiveness of learning organisation practices has a positive impact on the cottage and small industries' performance, mutually reinforcing and acceptable relationship. This study may provide meaningful implications for policy makers, entrepreneurs, managers, and researchers. However, this study was not able to capture complete and fully representative information from all relevant respondents. So it may further extend to different sectors, such as education, manufacturing, healthcare and industries.